(untitled) (Journal of Family Sciences, 2023)
Communication anxiety needs to be handled by the family from an early age because it can have an impact on the process of establishing a child’s self-concept. This happens because children experience a phase of adaptation in a new environment, such as a school environment. The handling of children’s communication anxiety is carried out by family communication and games. The purpose of this article is to describe the state of the art about children’s communication anxiety and games using the literature review method in a scientific journal for two years (2022-2023). As a result, ten journals specifically discuss anxiety in early childhood and various media games, four journals in 2022 and eight journals in 2023. The game media used to reduce anxiety in early childhood are hand puppets, snake and ladders, puzzles, coloring and origami, and roleplaying. The game media is considered capable of overcoming the problem of child anxiety because the child world is playing so children can describe their emotions better.